A tool for pathline creation using TOUGH simulation results and fully unstructured 3D Voronoi grids. (May 2019) - Bonduà, S.; Bortolotti, V.
Abstract: Pathline or streamline computation is used today to improve the understanding of fluid flow behavior in groundwater modelling. In particular, pathline computation on unstructured grids requires an accurate velocity interpolation method when the flow velocity field is given by numerical simulators only at the faces of the grid blocks; as for example in the case of the Integral Finite Difference method is used for spatial discretization. In the case of 3D Voronoi unstructured grids, a corner velocity interpolation (CVI) method allows continuous velocity field interpolation while preserving the mass conservation principle. We have developed a computer code, named TOUGH2Path, able to compute the velocity field based on the CVI method and generalized barycentric coordinates for 3D Voronoi polytope grid blocks tailored for the TOUGH family of codes. Results for the classical quarter five spot problem show that the coded algorithm correctly reproduces the pathlines computed with semi-analytical methods. Highlights: TOUGH2Path is a pathlines computation software tool for the TOUGH family of codes. The velocity field estimation method implemented is valid for fully 3D Voronoi grids. TOUGH2Path results are vtk xml files usable with open source visualization software.